Readability of amplitude modulation (AM) transmitter and receiver laboratory manual / Mohd Shahrul Ridzuan Zana Abidin - Zana Abidin, Mohd Shahrul Ridzuan (2012)
This research paper investigates about the readability of Amplitude Modulation Transmitter and Receiver Lab Manual. Recent research has indicated that the lack of procedure, the structure of the manual lab and the complexity of the words or phrase used in the manual are the main factor UiTM Engineering students are not capable of fully comprehending this lab manual. This research used three (3) readability software such as, Flesch Reading Ease, Flesch-Kincaid Grade Level and Gunning Fog Index. The Flesch Reading Ease factor was identified as 69.5 while the Flesch Kincaid Grade Level was determined at 5.8. In addition, the Gunning Fog Index test result yields a score of 8.1. These results indicate that the lab manual should be easily read and understood by 12 years old American student. During the research, changes were made to improve the readability factor. Further analysis of the lab manual, the readability test result indicates that the readability of the Flesch Reading Ease factor was identified as 63 while the Flesch Kincaid Grade Level was determined at 7.4 and the Gunning Fog Index test result yields a score of 10.4. Even though the readability factor has generally increased, the changes made were deemed necessary.